Building Blocks of Effective Leadership - Katherine Frank; Kristi Haik; Royce Smith (Academic Chairpersons Conference Proceedings, 2019)
Three individuals will share their perspectives about mentoring and guidance within academia. They will discuss how the networking, questioning and formation of feedback opportunities in their relationships have contributed to their evolution as administrators—from department chair to provost.
Keywords: Mentorship; career advancement; relationships; leadership; trust